The Pattern of Leadership of Kiai in Managing Learning Pesantren - Farid Wajdi; Achmad Sanusi; Dedi Mulyasana; Sofyan Sauri; Ahmad Khori; Saepuloh Saepuloh (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to describe the pattern of the leadership of Kiai and activities Pondok Pesantren Buntet Cirebon West Java. The method used is qualitative descriptive. In conclusion: (1) the Leadership of Kiai in organizing and managing pesantren Buntet shows responsibility, attention, full of appeal and a big influence for the students. Attitudes, behavior, and actions Kiai observed and interpreted by the students in the life sehani-day in pesantren Buntet. (2) Pesantren Buntet manages the learning shalaf with the system sorogan, wetonan, halaqah, and Bahtsul Masa ‘il and Khalaf with the learning system of the modern and innovative. (3) the supporting Factors in managing learning in Pesantren Buntet: (a) lack of awareness, willingness, competence, and expertise of the Kiai sepuh and manager better. (b) maintaining the attitude and behavior of noble character. (c) the relationship of Kiai and santri, dan Kiai with the community very well. The inhibiting factor is: (a) minimal supporting infrastructure and facilities. (b) the limited education budget. (c) the limited local learning and infrastructure of learning. (d) the management of the boarding school of the weak and the Period of study for quite a long time. (4) the Efforts of the improvement and development of pesantren Buntet of endeavoring to overcome the obstacles faced Pesantren Buntet.